EFFECTS OF PLANT HORMONES AND EXTERNAL FACTORS IN PROPAGATION OF YELLOW FLOWER TEA BY CUTTINGS - Van Viet, Nguyen; Quang Trung, Do; Viet Ha, Tran (Journal of Forestry Science and Technology, 2019)
Yellow flower tea (Camellia sp.) are multiple purposes of high economic values, used as a nutritious beverage, medicine and ornamental plants. This paper shows results of the propagation of three Yellow flower tea species by cuttings. After microbial treatment by Benlat 0.5% for about 15 minutes, cuttings continued to be treated with plant growth regulators for 5 minutes, evaluating the results after 75 days. In this study, we investigated effects of plant hormone β- indol butyric acid (IBA) and external factors on the cutting propagation of C. tamdaoensis, C. flava and C. chrysantha. The results showed IBA at 150 ppm presents the best performance of cuttings for all three tested Camellias. Moreover, the position of cutting on a mother affected rooting of Yellow flower tea cuttings. The top and middle cuttings reached the survival rate of 75.33 - 80.67%, the root formation rate of 73.33 - 77.67%. In addition, light is a primary energy source necessary for photosynthesis, growth and development of plants. Shade light 50 percent as the survival rate of 87.45 - 93.34% evaluate the results after 60 days. The plant cutting method is suitable to propagating Yellow flower tea for breeding purpose serving conservation and pharmaceutical marketing.